Norms of Soft Law as a New Source of Financial Law of Russia - RUCHKINA, Gulnara; EREMIN, Sergey G.; ZALYUBOVSKAYA, Natalia V.; ROMASHKOVA, Irina I.; VENGEROVSKIY, Evgeniy L. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
The goal of this study is the analysis of norms of soft law as a new source of financial law in the Russian Federation. The methodological basis of the research of the problem involves General scientific dialectic method of scientific knowledge, especially legal methods (structural-functional, legal and dogmatic), methods, legal modeling, comparative and historical jurisprudence, as well a generic methods (analysis and synthesis, description, observation, induction and deduction, comparison, generalization, formal logical and systematic). A brief review of research on the topic of ʼsoft lawʼ, a definition of the term ʼsoft lawʼ. Conducted theoretical analysis of the concept of ʼsoft lawʼ. Analyzed the specific use of the norms of soft law as a new source of Finance. The examples and identifies advantages of the use of norms of soft law as a new source of Finance. In General, ʼsoft-lawʼ standards fill in the gaps of legal regulation, both in international and national aspect, complement legal rules by means of references, interpretations or direct reproduction in the official sources of law, and, in some cases, act as a subsidiary regulator of international legal relations. The introduction into the fabric of international financial law, soft law norms, on the one hand, will increase the risks contributing to arbitrarily interpret and apply financial rules, on the other – may cause enough skepticism about the use of norms of soft law as a new source of Finance. However, there is no doubt that relative certainty, is always better than uncertainty. Thus, norms of soft law as a new source of financial law in Russia should be considered as an effective way to reduce the uncertainty in the financial relations system as a real alternative to soft law norms are not so much rules of law, but rather the lack of legal regulation insinuations when the objective need in the settlement.